PENGARUH INSENTIF PAJAK TERHADAP PENGUNGKAPAN TECHNOLOGICAL CAPITAL DI MASA PANDEMI COVID-19 - Pane, Zulfikar Ikhsan Pane (FACULTY OF ECONOMICS AND BUSINESS FLORES UNIVERSITY, 2024)
Covid-19 pandemic caused a decline economic sector so Indonesian government took initiative to provide incentive for companies. During pandemic, technological development also growth increasingly massive so this research aims determine effect tax incentive to technological development through technological capital disclosure as proxy as well as research novelty. With 117 annual report observation in manufacturing companies, it found tax incentive positive significant to technological capital disclosure. It means, tax incentive used by companies to technological implementation and also support by director with technological education background.